Women embodied leaders : peacebuilding, protest, and professions - Thompson, Randal Joy; Topuzova, Lazarina N. (Transformative women leaders, 2024)
Throughout history women have struggled to reclaim their bodies from the meanings and assaults imposed on them by cultural practices, sexual mores, victimization, and concepts of how their bodies should be presented and managed in public, to intimate male partners, or in the workplace. Despite the images and expectations imposed on their bodies, women are increasingly claiming their bodies as their own through embodied somatic leadership, in protesting injustice, in promoting peace, and in working in a so-called "man's world." Why has embodied somatic leadership more recently become highlighted, and what conditions in the world have brought this approach to leadership under study and scrutiny? Women Embodied Leaders answers these questions, analyzing models of embodied somatic leadership, and how women use this leadership from a number of perspectives. The wholistic treatment of this leadership is a useful tool not only for researchers, practitioners, and activists, but also for educators in the fields of leadership and social justice. The Transformative Women Leaders Series is published in collaboration between the International Leadership Association (ILA) and Emerald Publishing. Celebrating women leaders and the leadership styles they employ to achieve success, the books in this series highlight successful context-specific leadership approaches and the moral qualities of endurance.